Guidance Note on the Fund's Transparency Policy. (Policy Papers; Policy Paper, 2010)
The global financial crisis has had a significant impact on low-income countries (LICs)' debt vulnerabilities. Recent debt sustainability analyses (DSAs) indicate that external and fiscal financing requirements have increased. In addition, standard measures of a country's capacity to repay debt?GDP, exports, and fiscal revenue?are expected to be permanently lower. On average, debt ratios are therefore expected to deteriorate in the near term, particularly for public debt.